Conducting a synchronous virtual multiple mini-interview using Webex for medical school admissions - Domes, Trustin; Bueckert, Sherrill; Tetyurenko, Ganna; Hall, Dave; Ironside, Avery; Stobart, Kent (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: COVID-19 pandemic restrictions abruptly changed the way interviews for medical school admissions have been conducted. This study is unique as it highlights the first successful virtual synchronous multiple mini interview (MMI) in Canada. Our low technical incident rate, troubleshooting strategies and approach may reassure other medical schools considering conducting a virtual MMI. Success was achieved with collaboration, a strong organizational and communication strategy, learning along the way and a priori contingency plans. Virtual interviewing in academic medicine is likely here to stay, and future work to highlight the impact on applicants will help to build on the diversity mission in undergraduate medicine admissions.